Peningkatan Partisipasi dan Peran Aktif Masyarakat Dalam Pengembangan Usaha Tani Lahan Pekarangan di Desa Muntuk, Kecamatan Dlingo, Kabupaten Bantul, Yogyakarta - Sudrajat Sudrajat (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
The aim of this community service activities are (1) to identify the potential of yard to be developed into yard farming; (2) to identify the level of public participation in the development of yard farming; and (3) to increase the community’s active role in the implementation of yard farming development. Implementation of the community service carried out in the village of the District Muntuk Dlingo.The activities are manifested into counseling and interviews to the public figures and civil society. Counseling is conducted using face-to-face interview and a discussion in regards to development of farm yard. Interview is conducted on public figures and civil society regardless to the participation on the counselling. The results found that the Muntuk Village has a big potential of yard to be developed as a farming yard. The result also found that Muntuk villagers have high participation rates and high active role to develop the program. Participation and active role of the community indicated a desire to try to take advantage of yard before the rainy season.